2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943864
|View full text |Cite
|
Sign up to set email alerts
|

Tongue-Supported Human-Computer Interaction systems: A review

Abstract: Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.Abstract-The tongue can substitute human sensory systems and has been used as a medium of input to help impaired patients communicate with the world. Innovative techniques have been employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The present study of FD patients found a positive correlation between fissured tongue and PHQ9; moreover, there are significant differences in PHQ9 between different types of fissured tongue. Thus, noninvasive and standardized tongue diagnosis should be further explored [22].…”
Section: Discussionmentioning
confidence: 99%
“…The present study of FD patients found a positive correlation between fissured tongue and PHQ9; moreover, there are significant differences in PHQ9 between different types of fissured tongue. Thus, noninvasive and standardized tongue diagnosis should be further explored [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, attempts are being made to design minimally invasive tongue-computer interface mechanisms and classify tongue position using machine learning techniques. Attention is also being paid to the cost and operational difficulty related issues of the TMIS's [7,[24][25][26].…”
Section: Operational and Functional Limitationsmentioning
confidence: 99%
“…The TMIS features included in our reported design were discussed with tertiary hospital staff whose expertise helped in enhancing the proposed criteria. These design features were incorporated in a minimally invasive tongue-supported interaction system, which uses a novel tongue position and movement monitoring method and could be mounted without a procedure [7,25]. Thus, the demanding and expensive procedure that discourages TMIS's application in real-life situations was avoided.…”
Section: Toward Building a Better Tmismentioning
confidence: 99%
See 1 more Smart Citation
“…Tongue-Machine Interaction Systems (TMIS's) have been used in lab settings for helping patients to communicate with computers, controlling domestic appliances and equipment and, navigating mobility support systems like wheelchairs. TMIS's could also assist vision-impaired people through tactile vision as they could substitute formperception [1][2][3][4][5][6][7][8]. TMIS's were also employed for improving human balance and preventing people from nonvoluntary fall using tongue as part of the biofeedback system [9].…”
Section: Introductionmentioning
confidence: 99%